Biomolecule-enabled liquid separation membranes: potential and recent progress - Faiz Izzuddin Azmi; Goh, Pei Sean; Ahmad Fauzi Ismail; Nidal Hilal; Wong, Tuck Whye; Mailin Misson (MDPI, 2022)
The implementation of membrane surface modification to enhance the performance of membrane-based separation has become a favored strategy due to its promise to address the trade-off between water permeability and salt rejection as well as to improve the durability of the membranes. Tremendous work has been committed to modifying polymeric membranes through physical approaches such as surface coating and ontology doping, as well as chemical approaches such as surface grafting to introduce various functional groups to the membrane. In the context of liquid separation membranes applied for desalination and water and wastewater treatment, biomolecules have gained increasing attention as membrane-modifying agents due to their intriguing structural properties and chemical functionalities. Biomolecules, especially carbohydrates and proteins, exhibit attractive features, including high surface hydrophilicity and zwitterionic and antimicrobial properties that are desired for liquid separation membranes. In this review, we provide an overview of the recent developments in biomolecule-enabled liquid separation membranes. The roles and potentials of some commonly explored biomolecules in heightening the performance of polymeric membranes are discussed. With the advancements in material synthesis and the need to answer the call for more sustainable materials, biomolecules could serve as attractive alternatives for the development of high-performance composite membranes.